2020
DOI: 10.3389/fvets.2020.597751
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Three Different Sterilization Methods of Tilapia Skin Dressing: Impact on Microbiological Enumeration and Collagen Content

Abstract: Tilapia fish skin has demonstrated promise as a stable and practical biological dressing to be used in wound and burn management. However, the appropriate sterilization technique of the Tilapia fish skin is crucial before its clinical application. The standard sterilization technique must eliminate harmful pathogens but maintain the structural and biochemical properties that could compromise the dressing function. This study investigated and compared the efficiency of three sterilizing agents; chlorhexidine gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Tilapia skin is also a highly available product, safe, innovative, and easy to apply materials. Thus, it could be suggested as a potential xenograft for treating burns and regenerative medicine 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tilapia skin is also a highly available product, safe, innovative, and easy to apply materials. Thus, it could be suggested as a potential xenograft for treating burns and regenerative medicine 3 .…”
Section: Introductionmentioning
confidence: 99%
“…However, collagen integrity should be considered in the sterilization of fish skin grafts along with the efficient antimicrobial effect of the sterilizing agent. In a previous study, Ibrahim et al 3 , investigated that the silver nanoparticles (Ag NPs) explored advantage over both; chlorhexidine gluconate 4% and povidone iodine 10% in sterilizing of fish skin based on the microbial count and the collagen fiber integrity. However, this study had a limited use of one concentration of Ag NPs (25 µg/mL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen, the general name of a series of proteins with molecular weight (Mw) ~300,000, is the most abundant protein in animal body and the major component of skin and skeletal muscle tissues (Chen et al, 2008;Arias et al, 2018;Le Corre-Bordes et al, 2018;Bi et al, 2019;Dippold et al, 2019;Ibrahim et al, 2020;García-Hernández et al, 2021;Hernández-Rangel and Martin-Martinez, 2021). To date, over 20 different types of collagen have been detected in human body, the most common being collagen types I-IV.…”
Section: Collagenmentioning
confidence: 99%
“…Therefore, the extraction of collagen from Tilapia skin (FC) and further development and utilization can not only increase the added value of products, but also avoid resource waste and reduce environmental pollution [ 2 ]. It has also been reported that the Tilapia skin collagen film-forming property is significantly better than that of freshwater fish such as carp ( Hypophthalmichthys molitrix ) and grass carp ( Ctenopharyngodon idella ) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%